A multifunctional polymer electrolyte enables ultra-long cycle-life in a high-voltage lithium metal battery. Issue 5 (21st March 2018) - Dong, Tiantian; Zhang, Jianjun; Xu, Gaojie; Chai, Jingchao; Du, Huiping; Wang, Longlong; Wen, Huijie; Zang, Xiao; Du, Aobing; Jia, Qingming; Zhou, Xinhong; Cui, Guanglei
Abstract : We demonstrate a bacterial cellulose supported multifunctional polymer electrolyte for a 4.45 V-class LiCoO2 lithium metal battery. Abstract : In this article, we demonstrated for the first time an ultra-strong bacterial cellulose supported poly(methyl vinyl ether- alt -maleic anhydride) as a multifunctional polymer electrolyte for a 4.45 V-class LiCoO2 lithium metal battery. Such a polymer electrolyte based LiCoO2 lithium metal battery delivered significant capacity retention (85% retention after 700 cycles) at 60 °C. A more thorough investigation elucidated that it played multiple roles in enhancing the electro-oxidative resistance and reversible lithium plating/stripping of a LiCoO2 lithium metal cell. These extraordinary features open up a new avenue for the fabrication of advanced polymer electrolytes for high-voltage lithium metal cells.